2018
DOI: 10.12659/msm.908021
|View full text |Cite|
|
Sign up to set email alerts
|

Astragalus Polysaccharide Protects Neurons and Stabilizes Mitochondrial in a Mouse Model of Parkinson Disease

Abstract: BackgroundAstragalus polysaccharides (APS) have a very good therapeutic effect in the treatment of neurodegenerative diseases and nerve injury disease. However, research on Parkinson disease (PD) treatment with APS is lacking.Material/MethodsThe present study was designed to explore the effects of APS on the protection of neurons and mitochondrial in a mouse model of PD using behavioral experiments, and observations of mitochondrial structure and transmembrane potential.ResultsIt was shown that APS could atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…It was confirmed that APS could attenuate MPTP-induced motor dysfunction, increase the proportion of TH-positive cells, reverse MPTP-induced mitochondrial structural damage and reduce MPTP-induced high levels of ROS and increase MPTP-induced decrease in mitochondrial membrane potential. Moreover, APS also decreased the bax/bcl2 ratio and cytochrome-c and caspase-3 protein expression in substantia nigra in a mouse PD model [202]. Similarity, APS was shown to have the protective effect against 6-hydroxydopamine (an oxidative metabolite of dopamine) induced PD, which is likely due to the alleviation of oxidative stress and regulation of the apoptosis pathway and cholinergic system [203] (Figure 6⑧).…”
Section: Pharmacological Activitiesmentioning
confidence: 90%
“…It was confirmed that APS could attenuate MPTP-induced motor dysfunction, increase the proportion of TH-positive cells, reverse MPTP-induced mitochondrial structural damage and reduce MPTP-induced high levels of ROS and increase MPTP-induced decrease in mitochondrial membrane potential. Moreover, APS also decreased the bax/bcl2 ratio and cytochrome-c and caspase-3 protein expression in substantia nigra in a mouse PD model [202]. Similarity, APS was shown to have the protective effect against 6-hydroxydopamine (an oxidative metabolite of dopamine) induced PD, which is likely due to the alleviation of oxidative stress and regulation of the apoptosis pathway and cholinergic system [203] (Figure 6⑧).…”
Section: Pharmacological Activitiesmentioning
confidence: 90%
“…TH was a synthetic rate limiting enzyme of dopaminergic neurons, which was positively correlated with dopaminergic neurons. Accordingly, TH has been speculated to play some important roles in the pathophysiology of PD [19]. Thus, promoting the proliferation of TH-positive cells would help in the prevention and treatment of PD.…”
Section: Discussionmentioning
confidence: 99%
“…APS also could restore the morphologic changes induced by oxidative stress [20]. In a mouse Parkinson disease model, APS was reported to provide a protective effect on neurons by maintaining the mitochondrial structure and transmembrane potential [21]. In addition, APS could impede mitochondrial dysfunction and inhibit apoptosis in mesenchymal stem cells induced by iron overload [22].…”
Section: Introductionmentioning
confidence: 99%